Kesantunan dalam Berbahasa Inggris Pramusaji: Kasus pada Beberapa Café di Pantai Jimbaran, Bali - Ni Wayan Pastini (JURNAL BISNIS HOSPITALITI, 2021)
The aim of this research is to find out the understanding and ability of the waiters or waitresses to communicate in good English, especially apologizing, offering help, offering foods and drinks and the use of greetings in good English, so as to provide better service to tourists who come to enjoy foods and beverages in cafes of Jimbaran Beach. The data of this study were the expressions used by the waiters or waitresses of some cafes in Jimbaran Beach, chosen by accidentally. The language expressions used by the waiters or waitresses were recorded, transcripted and analysed. The results showed that some waiters or waitresses used expressions incorrectly and culturally inappropriate. It indicated that their ability in communicating in English in terms of accuracy and fluency needed to be improved. In addition, they had lack of understanding of cultural differences.